Preparation and application of double-sided aluminized polyimide film for ultralow-temperature multilayer vacuum insulation
By forming an aluminum-plated layer with a specific structure on the surface of a polyimide film, and combining it with anti-aging agents, low-temperature modifiers, and silane coupling agents, the problems of anti-aging and toughness of polyimide films at ultra-low temperatures are solved, achieving highly efficient multilayer vacuum insulation performance.
Patent Information
- Application Number
- CN202511690312.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-02-06
AI Technical Summary
Existing polyimide films for ultra-low temperature multilayer vacuum insulation have shortcomings in terms of aging resistance and low-temperature toughness. Traditional modifiers have poor dispersibility, and nanofillers are prone to agglomeration, making it difficult to meet the stringent operating conditions of ultra-low temperature multilayer vacuum insulation.
By employing a specific structure of anti-aging agent and low-temperature modifier working synergistically, combined with silane coupling agent and leveling agent, an aluminum layer is formed on the surface of a polyimide-based film through vacuum evaporation, forming a dense, low-porosity thin film structure that ensures uniform dispersion and interfacial bonding of all components.
It has achieved a thin film with excellent anti-aging properties, outstanding low-temperature toughness, and stable mechanical properties in ultra-low temperature environments, which extends service life and is suitable for ultra-low temperature multilayer vacuum insulation scenarios.
Smart Images

Figure CN121471705A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polyimide film preparation, and particularly relates to a kind of ultra-low temperature multilayer vacuum insulation double-sided aluminum-coated polyimide film preparation and its application. BACKGROUND
[0002] In the field of ultra-low temperature multilayer vacuum insulation, such as LNG storage and transportation, superconducting device insulation, etc., the insulation material needs to have excellent ultra-low temperature resistance, aging resistance and mechanical toughness, and the double-sided aluminum-coated polyimide film becomes one of the core substrates in this field because it has high barrier property and mechanical strength. However, the polyimide film prepared by the existing technology still has obvious shortcomings in practical application, which cannot meet the requirements of harsh working conditions.
[0003] From the aspect of aging resistance, the ultra-low temperature insulation environment is often accompanied by temperature cycle fluctuation, residual oxygen and trace ultraviolet radiation. The traditional polyimide film is prone to molecular chain degradation or oxidative crosslinking, which increases the brittleness of the film and reduces the barrier property. The commonly used anti-aging agents such as hindered phenol and phosphite have poor dispersibility at ultra-low temperature, and have insufficient compatibility with the polyimide matrix. After long-term use, they are prone to precipitation, which cannot continuously play the role of anti-aging, thereby shortening the service life of the insulation system and increasing the maintenance cost.
[0004] In terms of mechanical toughness (toughening), the pure polyimide material itself has strong molecular chain rigidity, which is prone to brittleness in the ultra-low temperature environment (below -196℃), and is prone to cracking under external force impact or vibration, which leads to damage of the aluminum coating and failure of the vacuum insulation structure. The existing toughening modification methods mainly use the addition of rubber elastomers or flexible polymer segments, but the interface bonding force between such modifiers and the polyimide matrix is weak, which is prone to phase separation at low temperature. Not only can it not effectively improve the toughness, but also it can reduce the tensile strength and dimensional stability of the film, which is difficult to balance the requirements of toughness and mechanical properties. In addition, the introduction of nano fillers (such as nano silicon dioxide) can improve the mechanical properties of the film to a certain extent, but the nano particles are prone to agglomeration in the traditional process, which cannot be uniformly dispersed in the polyimide matrix, but forms stress concentration points, which further aggravates the risk of brittle fracture of the film at low temperature. Therefore, it is a key direction to develop a double-sided aluminum-coated polyimide film with high-efficiency anti-aging property and excellent low-temperature toughness, which can solve the material bottleneck in the field of ultra-low temperature multilayer vacuum insulation. SUMMARY
[0005] The purpose of the present application is to solve the problems of poor anti-aging performance, poor low-temperature toughness and easy agglomeration of nano fillers in the prior art, and to provide a kind of double-sided aluminum coated polyimide film for ultra-low temperature multilayer vacuum insulation, which has excellent anti-aging performance, good ultra-low temperature toughness and stable mechanical properties, and is suitable for ultra-low temperature insulation scene.
[0006] To achieve the above purpose, the technical scheme adopted by the present application is: a kind of double-sided aluminum coated polyimide film for ultra-low temperature multilayer vacuum insulation, characterized by polyimide base film and aluminum coating layer formed on both surfaces by vacuum evaporation method; The polyimide base film is made of raw materials containing the following mass formula: 100 parts of pyromellitic dianhydride, 4,4'-diamino diphenyl ether, low temperature resistant modifier 5-15 parts, nano silica filler 3-8 parts, leveling agent 0.5-2 parts, anti-aging agent 0.5-1.5 parts, silane coupling agent 3-6 parts, polyvinyl chloride 5-15 parts; The molar ratio of 4,4'-diamino diphenyl ether to pyromellitic dianhydride is 1:1;The anti-aging agent is a compound represented by chemical formula 1; The structure of chemical formula 1 is: ; R1 in the chemical formula 1 is a substituent group, and R1 is selected from any one of the following: 、 The * in the substituent group is a linking site.
[0007] Further, the low temperature resistant modifier is hydroxyl silicone oil, and the hydroxyl content is 0.5-3%.
[0008] Further, the particle size of the nano silica filler is 10-50nm.
[0009] Further, the leveling agent is at least one of diacetone alcohol, polydimethylsiloxane, polymethylalkylsiloxane, organically modified polysiloxane, acrylic resin, urea-formaldehyde resin, melamine formaldehyde resin, fluorine modified acrylate and fluorocarbon compound.
[0010] Further, the silane coupling agent is selected from at least one of KH550 and KH560. ; .
[0011] A preparation method of a double-sided aluminum-plated polyimide film for ultra-low temperature multilayer vacuum insulation, comprising the following steps: a. Polyamide acid resin synthesis: under inert gas protection, the 4,4'-diamino diphenyl ether is dissolved in a polar aprotic solvent, after stirring uniformly, the phthalic anhydride is added in batches, the reaction temperature is controlled at 0-10℃, and the reaction is carried out for 4-8 hours to obtain a polyamide acid resin solution; b. Formula mixing: the low-temperature resistant modifier, nano-silicon dioxide filler, leveling agent, anti-aging agent, silane coupling agent and polyvinyl chloride are sequentially added into the polyamide acid resin solution, continuous stirring is carried out for 2-4 hours, so that they are fully mixed and uniform, and vacuum degassing is carried out to obtain a casting solution; c. Casting and imidization: the casting solution is cast on a clean steel belt or release paper, and is heated and cured through gradient temperature rising to form a polyimide-based film; d. Double-sided aluminum plating: the polyimide-based film is placed in a high-vacuum plating equipment, an aluminum layer is evaporated on both surfaces of the base film by using an electron beam evaporation source under the condition that the vacuum degree is better than 3.0×10 -3 Pa, to form the double-sided aluminum-plated polyimide film for ultra-low temperature multilayer vacuum insulation; The gradient temperature rising procedure is: first, heat preservation at 80-120℃ for 30-60 minutes, then gradually heat to 200-250℃ for 30 minutes, and finally heat to 300-350℃ for 10-20 minutes.
[0012] Further, the polar aprotic solvent is one of N,N-dimethylacetamide, N-methyl pyrrolidone or dimethyl sulfoxide, and the solid content is controlled at 15%-25%.
[0013] Further, the thickness of the aluminum layer is controlled at 30-50 nanometers. Further, the step b is carried out under a nitrogen atmosphere.
[0014] Further, in the double-sided aluminum-plated polyimide film for ultra-low temperature multilayer vacuum insulation, the aluminum layer is used as a reflection screen, and the polyimide-based film acts as a heat preservation layer. The aluminum layer is prepared by an evaporation process, and is a dense evaporation layer with low porosity and high light reflectivity. The polyimide-based film layer has the characteristics of low water absorption and low dielectric constant. The whole film structure has excellent high-temperature resistance, and the internal structure is not easy to be damaged during long-term use, so that the service life is longer.
[0015] An ultra-low temperature multilayer vacuum insulation structure is composed of a plurality of double-sided aluminum-plated polyimide films for ultra-low temperature multilayer vacuum insulation and reflection screen materials which are alternately stacked, the films are separated by a spacer with low thermal conductivity, and the whole is packaged in a high-vacuum environment.
[0016] Application of an ultra-low temperature multilayer vacuum insulation structure in ultra-low temperature components of liquid hydrogen and liquid nitrogen storage and transportation equipment, space probes, or superconducting magnet insulation systems.
[0017] In the anti-aging agent molecule used in this invention, the phenolic hydroxyl group and the benzotriazole structure work synergistically to form a highly efficient anti-aging mechanism: the phenolic hydroxyl group, as a free radical scavenger, can provide active hydrogen to combine with free radicals generated by temperature cycling and trace ultraviolet radiation in the ultra-low temperature environment, thereby terminating the molecular chain degradation reaction initiated by free radicals and avoiding the problem of increased brittleness of the polyimide matrix due to oxidative crosslinking; at the same time, the benzotriazole structure can selectively absorb ultraviolet light, reducing the damage of ultraviolet light to the polyimide molecular chain, and its molecular structure has excellent compatibility with the polyimide matrix. Combined with the stabilizing effect of the phenolic hydroxyl group, it can prevent the anti-aging agent from precipitating at ultra-low temperatures.
[0018] This invention overcomes three core problems in existing technologies—poor anti-aging properties, weak low-temperature toughness, and easy agglomeration of nanofillers—through the synergistic formulation of various raw materials. Regarding the poor anti-aging properties, the anti-aging agent with a specific structure can capture free radicals generated by temperature cycling and ultraviolet radiation in ultra-low temperature environments, and also absorb ultraviolet radiation. Furthermore, its molecular structure exhibits excellent compatibility with the polyimide matrix and silane coupling agent, avoiding the defects of poor low-temperature dispersion and easy precipitation of traditional anti-aging agents, thus achieving long-lasting anti-aging effects. Regarding the weak low-temperature toughness, the low-temperature resistant modifier hydroxyl silicone oil works synergistically with polyvinyl chloride, and the two can form a tight bond with the polyimide matrix. The tight interface bonding avoids the phase separation problem of traditional rubber elastomer modification, while improving the low-temperature ductility of the film and balancing toughness, tensile strength, and dimensional stability. To address the problem of easy agglomeration of nanofillers, nano-silica, under the action of silane coupling agent, can form stable chemical bonds with the polyimide matrix and other components, achieving uniform dispersion, avoiding stress concentration, and helping to enhance mechanical properties. In addition, leveling agent ensures the uniformity of film formation in the casting solution, and combined with gradient temperature imidization process, ensures that the synergistic effect of each component is fully exerted, ultimately making the double-sided aluminized polyimide film suitable for ultra-low temperature multilayer vacuum insulation scenarios.
[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. Superior anti-aging performance: The anti-aging agent with a specific structure works synergistically with the phenolic hydroxyl group and benzotriazole structure to capture free radicals and absorb ultraviolet rays. It also has good compatibility with the polyimide matrix, avoiding precipitation at low temperatures. This solves the problems of poor low-temperature dispersion and easy failure of traditional anti-aging agents, thus extending the service life of the film.
[0020] 2. Enhanced low-temperature toughness: The low-temperature modifier hydroxyl silicone oil works synergistically with polyvinyl chloride to form a tight interfacial bond with the polyimide matrix, avoiding the phase separation problem of traditional modification, improving the ultra-low temperature ductility of the film, balancing toughness, tensile strength, and dimensional stability, and reducing the risk of low-temperature brittleness.
[0021] 3. More stable overall performance: Silane coupling agent helps nano-silica to be uniformly dispersed in the matrix, avoiding agglomeration and stress concentration. This not only enhances mechanical properties, but also, together with leveling agent and gradient heating process, ensures film uniformity. Ultimately, the film has excellent mechanical and thermal insulation properties in ultra-low temperature environments, making it suitable for ultra-low temperature multilayer vacuum insulation scenarios. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the structure of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation according to the present invention; 1 is a polyimide-based film, and 2 is an aluminum-plated layer.
[0023] Figure 2 This is the NMR spectrum of the anti-aging agent 1 described in this invention.
[0024] Figure 3 This is the NMR spectrum of intermediate 1 described in this invention. Detailed Implementation
[0025] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Preparation Example 1 Preparation of anti-aging agent 1: ; ; CAS number of compound 1: 95-14-7; CAS number of compound 2: 115997-68-7; CAS number of compound 3: 40248-01-9; Intermediate 1 and anti-aging agent 1 are new compounds without CAS numbers.
[0027] Under a nitrogen atmosphere, 15.00 g of compound 1, 34.44 g of compound 2, 24.20 g of sodium tert-butoxide, and 200 mL of toluene were added sequentially to the reaction system. The mixture was stirred until homogeneous, then 4.37 g of tetrakis(triphenylphosphine)palladium was added. The mixture was heated to 120 °C and refluxed for 12 h. After the reaction was complete, the temperature was slightly lowered, and the mixture was filtered through silica gel. The filtrate was cooled to room temperature, washed three times with water, and the organic phase was retained. The aqueous phase was then extracted with toluene. The combined organic phases were dried over anhydrous magnesium sulfate, and the solvent was removed using a rotary evaporator. The mixture was evaporated to dryness, and silica gel column chromatography was performed using a mixture of petroleum ether and ethyl acetate as eluent. The resulting product was evaporated to dryness to give 31.24 g of intermediate 1. The mass spectrometry of the compound was analyzed by MS+H. + 328, see MRI Figure 3 Under a nitrogen atmosphere, 31.24 g of intermediate 1, 13.26 g of compound 3, 18.32 g of sodium tert-butoxide, and 350 ml of toluene were added sequentially to the reaction system. The mixture was stirred until homogeneous, then 3.30 g of tetrakis(triphenylphosphine)palladium was added. The temperature was raised to 120 °C and refluxed for 12 h. After the reaction was complete, the temperature was slightly lowered, and the mixture was filtered using silica gel. The filtrate was cooled to room temperature, washed three times with water, and the organic phase was retained. The aqueous phase was then extracted with toluene. The combined organic phases were dried over anhydrous magnesium sulfate, and the solvent was removed using a rotary evaporator. The mixture was evaporated to dryness, and silica gel column chromatography was performed using a mixture of petroleum ether and ethyl acetate as eluent. The resulting product was evaporated to dryness, yielding 29.38 g of anti-aging agent 1. The compound was analyzed by mass spectrometry (MS+H). + :415, see MRI Figure 2 .
[0028] Preparation Examples 2-4 In Preparation Examples 2-4, anti-aging agents 2-4 were prepared sequentially, following the preparation method of Preparation Example 1, except that compound 3 was replaced, and the rest remained the same as in Preparation Example 1. See Table 1 for details.
[0029] Table 1 Example 1 Preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation; 1. Raw material components: Pyromellitic dianhydride: 100 parts, purchased from: Hubei Xinjiecheng Chemical Technology Co., Ltd.; The molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic dianhydride was 1:1, and it was purchased from Beijing Hailiyang Chemical Technology Co., Ltd. Low-temperature resistant modifier: hydroxyl silicone oil, 10 parts, hydroxyl content 0.5-3%, purchased from: Anhui Aiyota Silicone Oil Co., Ltd.; Nano-silica filler: 5 parts, average particle size 15nm, purchased from: Suzhou Meibang Nanomaterials Co., Ltd. Leveling agent: polydimethylsiloxane, 1 part, purchased from: Shanghai Dingfen Chemical Technology Co., Ltd.; Anti-aging agent: 1 part of the anti-aging agent 1 obtained in Preparation Example 1; Silane coupling agent: KH550, 4 parts, purchased from: Shandong Bosheng Chemical Co., Ltd.; Polyvinyl chloride: 10 parts, purchased from Ningxia Jinyuyuan Chemical Group Co., Ltd.; Polar aprotic solvent: N,N-dimethylacetamide, purchased from Jinan Chuangshi Chemical Co., Ltd.
[0030] 2. Preparation method: a. Synthesis of polyamic acid resin: Under nitrogen protection, 100 parts of 4,4'-diaminodiphenyl ether were dissolved in N,N-dimethylacetamide to prepare a solution with a solid content of 20%, and stirred for 30 minutes until completely dissolved. The system temperature was controlled at 5°C, and pyromellitic dianhydride was added to the solution in batches. After the addition was complete, the temperature was maintained at 5°C, and the reaction was continued for 6 hours to obtain a homogeneous and transparent polyamic acid resin solution. b. Formulation mixing: Transfer the above polyamic acid resin solution to a nitrogen-protected stirred tank, and add 10 parts of hydroxyl silicone oil, 5 parts of nano silica filler, 1 part of polydimethylsiloxane, 1 part of anti-aging agent 1, 4 parts of KH550 and 10 parts of polyvinyl chloride in sequence. Start stirring and control the speed at 300 r / min. Continue stirring for 3 hours until all components are completely mixed and uniform. Then perform vacuum degassing treatment (vacuum degree -0.095MPa, time 30 minutes) to obtain a bubble-free, uniform and stable casting solution. c. Casting and Imidization: The casting solution is uniformly cast onto a clean stainless steel strip using a casting machine, with the casting thickness controlled at 0.1 mm. The cast wet film is then placed in a hot air oven for gradient temperature imidization: first, it is held at 100℃ for 45 minutes to remove the solvent; then, the temperature is gradually increased to 220℃ and held for 30 minutes for pre-imidization; finally, the temperature is increased to 320℃ and held for 15 minutes to complete the imidization. After cooling to room temperature, it is peeled off from the steel strip to obtain a polyimide-based film. d. Double-sided Aluminum Coating: The above polyimide-based film is placed in a high-vacuum coating equipment, and a vacuum is drawn to a vacuum level of 3.0 × 10⁻⁶. -3 Pa; Using an electron beam evaporation source, high-purity aluminum wire (purity ≥99.99%) was heated and evaporated, and aluminum layers were deposited on both surfaces of the base film, with the thickness of the aluminum layer controlled at 30 nm. After evaporation, it was naturally cooled to room temperature to obtain a double-sided aluminum-coated polyimide film for ultra-low temperature multilayer vacuum insulation.
[0031] Examples 2-4 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out by referring to the preparation method of Example 1, except that the anti-aging agent is replaced with anti-aging agent 2-anti-aging agent 4 in sequence, and the rest is the same as in Example 1.
[0032] Comparative Example 1 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out by referring to the preparation method of Example 1, except that the anti-aging agent is replaced with the antioxidant MDA, and the rest is the same as in Example 1.
[0033] Comparative Example 2 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out by referring to the preparation method of Example 1, except that the anti-aging agent is replaced with the antioxidant MMB, and the rest is the same as in Example 1.
[0034] Comparative Example 3 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out by referring to the preparation method of Example 1, except that the anti-aging agent is replaced with anti-aging agent DNP, and the rest is the same as in Example 1.
[0035] Comparative Example 4 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out according to the preparation method of Example 1, except that the anti-aging agent is not added, and the rest is the same as in Example 1.
[0036] Comparative Example 5 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out according to the preparation method of Example 1, except that the low temperature resistant modifier is not added, and the rest is the same as in Example 1.
[0037] Comparative Example 6 The preparation of a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation is carried out according to the preparation method of Example 1, wherein the thickness of the aluminized layer is 20 nm, and the rest is the same as in Example 1.
[0038] Performance testing: Test sample: A double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation prepared in the examples and comparative examples.
[0039] 1. Tensile property test: The tensile strength of the sample was tested according to the test method of GB / T 1040.3-2006. The data are shown in Table 2.
[0040] 2. Freeze-thaw aging stability test: The test sample was stored in a liquid nitrogen environment at -196℃ for 5 hours, then heated to 80℃ and stored for 5 hours. This process was repeated 150 times. The tensile strength was then measured again, and the tensile strength retention rate was calculated. The data are shown in Table 2.
[0041] 3. UV stability test: The test sample was placed in a UV aging chamber with a UV wavelength of 340nm and an irradiation intensity of 0.68W / m². 2 The temperature was 60℃, the humidity was 50%, and the aging time was 3000h. The tensile strength was retested, and the tensile strength retention rate was calculated. The data are shown in Table 2.
[0042] 4. Vacuum insulation performance test: Refer to the test method of GB / T 10294-2008. Test conditions: vacuum degree ≤ 3.0 × 10⁻⁶. -3 Pa, cold end temperature -196℃, hot end temperature -23℃, 10 layers of thin film, the laminated insulation structure was placed in a vacuum insulation test device, and the thermal conductivity was measured after stabilization for 24 hours. The data are shown in Table 2.
[0043] Table 2 The tensile properties of the embodiments remained generally stable, exhibiting superior performance retention in both freeze-thaw aging and UV aging tests, and also demonstrating more outstanding vacuum insulation performance. In contrast, the comparative examples with traditional anti-aging agents replaced or not added showed a significant decrease in UV aging resistance, and their freeze-thaw aging performance was also inferior to that of the embodiments. The comparative examples lacking low-temperature modifiers showed a substantial decline in freeze-thaw aging performance, and their vacuum insulation performance was also affected. The comparative examples with reduced aluminum plating thickness showed a significant decrease in both tensile properties and vacuum insulation performance, with only aging performance retention similar to some embodiments. Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation, characterized in that, It consists of a polyimide-based film (1) and an aluminum-plated layer (2) formed on both of its surfaces by vacuum evaporation. The polyimide-based film (1) is made from raw materials comprising the following parts by weight: 100 parts pyromellitic dianhydride, 4,4'-diaminodiphenyl ether, 5-15 parts low-temperature modifier, 3-8 parts nano-silica filler, 0.5-2 parts leveling agent, 0.5-1.5 parts anti-aging agent, 3-6 parts silane coupling agent, and 5-15 parts polyvinyl chloride; The molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic dianhydride is 1:1; the anti-aging agent is a compound represented by chemical formula 1; The structure of chemical formula 1 is as follows: ; R1 in chemical formula 1 is a substituent, and R1 is selected from: methyl, phenyl, ... , Any of the following, where * in the substituent is the linking site.
2. The ultra-low temperature multilayer vacuum insulation double-sided aluminized polyimide film according to claim 1, characterized in that, The low-temperature resistant modifier is hydroxyl silicone oil with a hydroxyl content of 0.5-3%.
3. The ultra-low temperature multilayer vacuum insulation double-sided aluminized polyimide film according to claim 1, characterized in that, The particle size of the nano-silica filler is 10-50 nm.
4. The ultra-low temperature multilayer vacuum insulation double-sided aluminized polyimide film according to claim 1, characterized in that, The leveling agent is at least one of diacetone alcohol, polydimethylsiloxane, polymethylalkylsiloxane, organically modified polysiloxane, acrylic resin, urea-formaldehyde resin, melamine-formaldehyde resin, fluorinated acrylate, and fluorocarbon compound.
5. The ultra-low temperature multilayer vacuum insulation double-sided aluminized polyimide film according to claim 1, characterized in that, The silane coupling agent is selected from at least one of KH550 and KH560.
6. The ultra-low temperature multilayer vacuum insulation double-sided aluminized polyimide film according to claim 1, characterized in that, The anti-aging agent is any one of the compounds shown in the following structures: ; 。 7. A method for preparing a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation as described in any one of claims 1-6, characterized in that, Includes the following steps: a. Polyamic acid resin synthesis: Under inert gas protection, the 4,4'-diaminodiphenyl ether is dissolved in a polar aprotic solvent and stirred evenly. Then, the pyromellitic dianhydride is added in batches, and the reaction temperature is controlled at 0-10℃. The reaction is carried out for 4-8 hours to obtain a polyamic acid resin solution. b. Formulation mixing: The low-temperature resistant modifier, nano silica filler, leveling agent, anti-aging agent, silane coupling agent and polyvinyl chloride are added sequentially to the polyamic acid resin solution. The mixture is stirred continuously for 2-4 hours to ensure thorough and uniform mixing. The solution is then degassed under vacuum to obtain the casting solution. c. Casting and imidization: The casting solution is cast onto a clean steel strip or release paper and cured by gradient heating to form a polyimide-based film; d. Double-sided aluminum plating: The polyimide-based film is placed in a high-vacuum coating apparatus, with a vacuum degree better than 3.0 × 10⁻⁶. -3 Under the condition of Pa, an electron beam evaporation source is used to deposit aluminum layers on both surfaces of the base film to form the aforementioned ultra-low temperature multilayer vacuum insulation double-sided aluminum-coated polyimide film; the gradient heating program is as follows: first, hold at 80-120℃ for 30-60 minutes, then gradually increase the temperature to 200-250℃ and hold for 30 minutes, and finally increase the temperature to 300-350℃ and hold for 10-20 minutes.
8. The method for preparing a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation according to claim 7, characterized in that, The polar aprotic solvent is one of N,N-dimethylacetamide, N-methylpyrrolidone, or dimethyl sulfoxide, and the solid content is controlled at 15%-25%.
9. The method for preparing a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation according to claim 7, characterized in that, The thickness of the aluminum plating layer is controlled at 30-50 nanometers.
10. The method for preparing a double-sided aluminized polyimide film for ultra-low temperature multilayer vacuum insulation according to claim 7, characterized in that, Step b is performed under a nitrogen atmosphere.